Testing General Relativity Using Large-scale Structure Photometric Redshift Surveys and the Cosmic Microwave Background Lensing Effect - Shang Li; Jun-Qing Xia (The Astrophysical Journal Supplement Series)
The E _G statistic provides a valuable tool for evaluating the predictions of general relativity (GR) by probing the relationship between gravitational potential and galaxy clustering on cosmological scales within the observable Universe. In this study, we constrain the E _G statistic using photometric redshift data from the Dark Energy Survey (DES) MagLim sample in combination with the Planck 2018 cosmic microwave background (CMB) lensing map. Unlike spectroscopic redshift surveys, photometric redshift measurements are subject to significant redshift uncertainties, making it challenging to constrain the redshift distortion parameter β with high precision. We adopt a new definition for this parameter, β ( z ) = fσ _8 ( z )/ bσ _8 ( z ). In this formulation, we reconstruct the growth rate of structure, fσ _8 ( z ), using the artificial neural network method, while simultaneously utilizing model-independent constraints on the parameter bσ _8 ( z ), directly obtained from the DES collaboration. After obtaining the angular power spectra ${C}_{\ell }^{gg}$ (galaxy–galaxy) and ${C}_{\ell }^{gκ }$ (galaxy–CMB lensing) from the combination of DES photometric data and Planck lensing, we derive new measurements of the E _G statistic: E _G = 0.354 ± 0.146, 0.452 ± 0.092, 0.414 ± 0.069, and 0.296 ± 0.069 (68% confidence limit) across four redshift bins z = 0.30, 0.47, 0.63, and 0.80, respectively, which are consistent with the predictions of the standard Lambda cold dark matter model. Finally, we forecast the E _G statistic using future photometric redshift data from the China Space Station Telescope, combined with lensing measurements from the CMB-S4 project, indicating an achievable constraint on E _G of approximately 1%, improving the precision of tests for GR on cosmological scales.